2017
DOI: 10.1177/1464419317731699
|View full text |Cite
|
Sign up to set email alerts
|

Contact simulation of soft micro/nano bioparticles for use in identification of mechanical properties and manipulation based on atomic force microscopy

Abstract: The aim of this paper is to develop and simulate elastic-perfectly plastic contact theories for proper determination and estimation of contact area in manipulation of micro/nano bioparticles. The nanoparticles studied in this paper are categorized into three different cancerous cell types, lowly (LNCaP) and highly metastatic human prostate cancer cells (CL-1, CL-2), two normal bladder cells (Hu609 and HCV29) and three cancerous bladder cells (Hu456, T24 and BC3726). First, Hertz elastic model, finite element, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…They used a spherical geometry to approximate the geometry of the cancer cells. Korayem et al [3] used soft particle contact mechanics to identify properties. Chim et al [4] studied and identified the visco-elastic properties of cancer cells by using the AFM.…”
Section: -Introductionmentioning
confidence: 99%
“…They used a spherical geometry to approximate the geometry of the cancer cells. Korayem et al [3] used soft particle contact mechanics to identify properties. Chim et al [4] studied and identified the visco-elastic properties of cancer cells by using the AFM.…”
Section: -Introductionmentioning
confidence: 99%